Telomere protection without a telomerase; the role of ATM and Mre11 in Drosophila telomere maintenance. - Bi, X.; Wei, S.C.; Rong, Y.S. (Current Biology, 2004)
The conserved ATM checkpoint kinase and the Mre11 DNA repair complex play essential and overlapping roles in maintaining genomic integrity. We conducted genetic and cytological studies on Drosophila atm and mre11 knockout mutants and discovered a telomere defect that was more severe than in any of the non-Drosophila systems studied. In mutant mitotic cells, an average of 30% of the chromosome ends engaged in telomere fusions. These fusions led to the formation and sometimes breakage of dicentric chromosomes, thus starting a devastating breakage-fusion-bridge cycle. Some of the fusions depended on DNA ligase IV, which suggested that they occurred by a nonhomologous end-joining (NHEJ) mechanism. Epistasis analyses results suggest that ATM and Mre11 might also act in the same telomere maintenance pathway in metazoans. Since Drosophila telomeres are not added by a telomerase, our findings support an additional role for both ATM and Mre11 in telomere maintenance that is independent of telomerase regulation.